Synthesis and characterization of electrodeposited cobaltiron nanoparticles on different substrates / Wan Normimi Roslini Abdullah - Abdullah, Wan Normimi Roslini (2013)
Environmental and health issues from the usage o f hard chromium coating as a protective layer for corrosion protection have caused concerns. Research on the use of nanocrystalline Cobalt-Iron as an environmentally friendly and a potential substitute for hard chromium coating on different metals such as Stainless Steel, Copper and Titanium corrosion protection is lacking. The objectives o f this research are to synthesize Cobalt-Iron nanoparticles on these three metal substrates in various deposition times and to discuss the characteristics and properties of the nanoparticles. Direct current electrodeposition process is used to prepare the nanoparticles samples using various precursors. Using constant temperatures o f 50±5 C and a variety of electrolyte compositions, the synthesis o f pure Cobalt gives the optimum electrolyte pH and precursor molarity. These results are then used for the synthesis o f Cobalt-Iron nanoparticles in several deposition times on different substrates. In an optimum deposition time, all substrates are folly coated by Cobalt-Iron nanoparticles with decreased crystallite and particle sizes. Corrosion rate decreases while microhardness increases with longer deposition time. Chromium element is unexpectedly found in Cobalt-Iron microstructures on Stainless Steel and believed to have reacted with the electrolyte. However, Chromium content is not found on Copper and Titanium substrates. Interestingly, Cobalt-Iron nanoparticles samples exhibit various surface morphologies. All nanoparticles samples demonstrate active corrosion without passivation and soft ferromagnetic behavior. The findings show that natural elemental composition and properties of metal substrates influence the characteristics and properties o f Cobalt-Iron nanoparticles and can be suggested as an alternative for hard chromium coating.